Risk Categories Disclosed in the Administration Reports of Brazilian Companies with ADRs - Zonatto, Vinícius Costa da Silva; Beuren, Ilse Maria (Review of Business Management, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The study aims to find the categories of risks disclosed in the Administration Reports of Brazilian companies with the issuance of ADR’s. The research is characterized as descriptive, accomplished through documentary analysis. The sample includes 28 Brazilian companies with the issuance of American Depositary Receipt (ADR’s) in the Stock Exchange of New York (USA). We have tried to identify the categories of risk, presented by the companies surveyed in the Administration Reports (AR) of 2007. Seven categories of corporate risks were considered, identified through COSO (2004) methodology: strategic risks, market risks, credit risks, liquidity risks, operational risks, legal risks and image risks. The survey results show that in general there is no standardization of the types of risks disclosed by the companies. A total of 14 types of risks have been identified. The predominant category in the disclosure was the operational risk, with 20.72% of the observations. There was no disclosure of image risk in the AR of the companies surveyed. It was found that 19 companies, 67.86% of the surveyed companies, demonstrate some kind of risk to which they are exposed. On the other hand, nine companies (32.14%) did not show any kind of risk. Key words: Disclosure. Risk categories. Administration reports.